Assessment of body mass index and its relationship with breast cancer survival in a clinical oncology service in the Federal District - Ferreira, Kamila Fernandes; Weis, Luiza Nardin; Assunção, Leandro Almeida; Oliveira, Eduarda Sabá Cordeiro de; Castro, Rafael Amaral de (Brazilian Journal of Oncology, 2022)
Objective: The purpose of this study was to analyze the relationship between obesity and clinical outcomes in breast cancer patients by evaluating the mean body mass index (BMI) and overall survival.Material and Methods: The research's method consisted of a retrospective observational and descriptive study without intervention, carried out in a public oncology service in Brazils Federal District. We selected breast cancer patients with hormonal expression positivity in follow-up from January 2016 to December 2020.Results: 305 female patients were evaluated, aged between 33 and 92 years old (average age of 59). Most patients were over 55 years old (63.3%). The mean weight of the patients was 71.70±9.10 kilograms. Regarding BMI, 38.7% of patients were classified as obese. As for the immunohistochemical classification (IHC), 72.9% of the patients were luminal B. Among the patients in which the initial treatment was registered, 56.1% received hormone therapy, while 43.9% received chemotherapy. The intention to treat in most patients was curative. Most patients had disease staging between II and III. As for the outcome, most patients were still undergoing treatment (83.0%) at the time of data collection. Correlating the IHC classification with patient survival, there was no significant difference between patient's classified as luminal A and those classified as luminal B (p: 0.342). There was also no significant difference between non-obese and obese patients in the assessment of overall survival and weight (p: 0.917).Conclusion: Despite the high prevalence of obesity in the studied population, the overall survival of this group did not differ from the non-obese group, even in the analyzes by IHC profile.
Keywords: Body mass index; Survival; Breast neoplasms